Pengaruh Latihan Resistance Band Terhadap Kemampuan Shooting Pemain Bola Basket Klub Rongqing Yayasan Fuqing Banjarmasin - Maulana, Ahmad; Barikah, Amalia (Jurnal Porkes, 2023)
Shooting a basketball is an ability that a basketball player must have to score points. To be a great shooter, in addition to mastering good shooting techniques, of course, it needs to be supported by physical elements in the player's body, such as arm muscle strength. One of the exercises to increase arm muscle strength is resistance band exercises. This exercise is expected to improve the ability to shoot basketball. This study aims to determine whether there is an effect of resistance band training on the shooting ability of basketball players at the Rongqing Club Banjarmasin. The research method used in this research is pre-experimental with the form of One Group Pretest-Posttest Design. The population in this study were 20 basketball athletes from the Rongqing Club Fuqing Foundation Banjarmasin, and the sample in this study were all 20 athletes. Sampling was done by total sampling technique. Measurements were made before and after the treatment was given. The effect of treatment was measured by the difference between the pretest and the posttest using the paired samples t-test. The results of the Paired Samples t-test showed a significance value of 0.000, less than 0.05. Thus it was concluded that there was an effect of resistance band exercise on the shooting ability of basketball athletes at the Rongqing Club Fuqing Foundation Banjarmasin